PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM PENANGGULANGAN KORBAN KONFLIK BERSENJATA PADA MASA INVASI RUSIA-UKRAINA - Pulungan, Rizka Nur Fadilah; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The study discussed the role of the International Committee of the Red Cross (ICRC) in handling victims of armed conflict during the Russian invasion of Ukraine in 2022-2023. The invasion generated a humanitarian crisis characterized by increasing civil casualties, waves of refugees, and violation of international humanitarians' laws. The research methods used are qualitative descriptive results in library studies and official document analysis of icrc, the UN report, and other relevant sources. The framework of the theory used is the perspective of pluralism and the theory of the international organization Clive Archer to explain the position of icrc as an independent actor in the norms, socialization, and operational functions of humanity. Studies have shown that icrc carried out civil evacuations, relief distribution, provision of health services, and visits on prisoners of war. However, icrc faces challenges of limited access, security risk, and conflict resistance. The study highlights the importance of international support to strengthen the capacity of icrc to ensure humanitarian protection during the russian-ukrainian conflict. Keywords: Armed Conflict, ICRC, Invasion, Russia, Ukraine.